Impacts of highly charged ions as seeds in a magneto-structural phase transition of magnetocaloric thin films. (July 2015) - Cervera, S; Trassinelli, M; Marangolo, M; Bernard-Carlsson, L; Eddrief, M; Etgens, V H; Gafton, V; Hidki, S; Lacaze, E; Lamour, E; Prigent, C; Rozet, J-P; et al.
Synopsis: Investigation on modifications of structural and magnetic properties of magnetocaloric thin films induced by slow highly charged ions bombardment under well-controlled conditions is presented. The ions induce defects/constraints that facilitate nucleation of one phase with respect to the other in the first-order magnetostructural MnAs, with a consequent suppression of thermal hysteresis, but without any significant perturbation on the other structural and magnetic properties.